The Effect Of Polymeric Fibers On The Properties Of Silty Soils (Journal of Hama University, 2024)
The technique of soil reinforcement by polymer fibers considered one of the recent procedures which aims to improve the soil specifications the research was based on conducting laboratory tests on three different types of silty soils mixed with polymer fibers at different proportions the results of the experiments were adopted in an relationship between the friction angle ,cohesion and modulus of elasticity by linking these specifications to the percentage of sand or clay present in silty soils.